Improving students' creative thinking skills through the project-based learning model integrated design thinking - Rozasqonain, Putri Laila; Muspiroh, Novianti; Roviati, Evi (IAIN Palangka Raya, 2025)
This research aims to analyze the application of the Design Thinking integrated PJBL model, analyze differences in increasing students' creative thinking abilities, and analyze student responses. The method used in this research is quasi-experimental with a pretest-posttest control group design. The sampling technique used was random sampling, using class X7 as the experiment and class X3 as the control. Data collection techniques use observation sheets, tests, and questionnaires. The research results show that implementing PJBL-Design Thinking can improve students' creative thinking abilities. This is proven by the assessment of student learning activities, which always increase at each stage, reaching 87% with very good criteria. There was a difference in the increase in students' creative thinking in the experimental and control classes; the average N-Gain indicator for the experimental class was obtained on average at 0.72 in the high category. Student responses to PjBL-Design Thinking learning obtained an average percentage of 80% with good criteria.